2019
DOI: 10.1038/s41598-019-40081-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving maize grain yield by matching maize growth and solar radiation

Abstract: Matching of maize growth with solar radiation is of great importance for achieving high yield. We conducted experiments using different maize cultivars and planting densities under different solar radiations during grain filling to quantitatively analyze the relationships among these factors. We found that a decrease in solar radiation after silking caused a drop in maize grain yield and biomass, with lower solar radiation intensities leading to worse grain yields and biomass. Cultivar ZD958 was more sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 32 publications
5
52
1
Order By: Relevance
“…Increasing plant density is an important way to improve maize grain yield, as was verified in our previous study 7 , 29 , 30 . In the present study, the grain yields were universally more than 11.0 Mg ha −1 (Table S1 ), and the highest obtained yield was 23.9 Mg ha −1 , which was obtained at a density of 10.5 plants m −2 (data not shown, Experiment II).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Increasing plant density is an important way to improve maize grain yield, as was verified in our previous study 7 , 29 , 30 . In the present study, the grain yields were universally more than 11.0 Mg ha −1 (Table S1 ), and the highest obtained yield was 23.9 Mg ha −1 , which was obtained at a density of 10.5 plants m −2 (data not shown, Experiment II).…”
Section: Discussionsupporting
confidence: 65%
“…In previous studies, through more than 10 years of field investigation at Qitai Farm in Xinjiang, China, we observed significant differences in grain yields 6 , 7 , 29 and different individual yield by visual observation in the border rows between different high-yield maize cultivars under high plant density. Based on the results of these studies, we hypothesized that the marginal superiority in the border rows could be used as an indicator of plant-density tolerance under high plant density.…”
Section: Introductionmentioning
confidence: 81%
“…Genetic background, environmental conditions, and geographic location can affect kernel composition in maize hybrid (Nuss & Tanumihardjo, 2010). Further, our findings showed that Xianyu 335 had the highest grain yield which was 12.80 Mg ha −1 at the 44°37′ N. Xianyu 335 had the higher yield potential (Yang et al., 2019) which used sufficient solar radiation and Zhongdan 909 showed the second‐highest grain yield which was found to be 12.76 Mg ha −1 at the latitude of 43°48′ N. While the maximum grain yield of hybrids Zhengdan 958, Nonghua 101, and Denghai 11 were 12.17, 12.17, and 10.93 Mg ha −1 respectively, at the latitudes of 44°28′, 43°39′, and 41°43′ N. From the obtained results, it can be found that each hybrid obtained the maximum grain yield at different latitudes. In general, the selection of genotype is also essential for KW and grain yield at different ecological conditions (latitudes).…”
Section: Discussionmentioning
confidence: 61%
“…This is most likely because radiation levels and temperature were both higher in Hainan during grain filling ( Supplementary Fig. 6), the stage at which a positive correlation between yield and solar radiation level has been established 38,39 . In traditional breeding, the generation of hybrid rice lines led to yield increases up to 50% per unit area compared with inbred lines 40,41 .…”
Section: Discussionmentioning
confidence: 99%